Perencanaan dan Perancangan Taman Budaya Aji Saka Dengan Pendekatan Konsep Neo-Vernakular di Kabupaten Grobogan - Retno Fitri Astuti; Arnida Dwi Roroyono (DPPM Universitas Pelita Bangsa, 2022)
Grobogan Regency is a Regency in Central Java which has a lot of culture and arts. The absence of facilities that accommodate articstic and cultural activities makes the public less aware and does not preserve the existing culture in Grobogan Regency. With these conditions, aplace for art and culture is needed so that people are more focused and not fall into negative associations. Seeing these needs and potentials, planning and designing a cultural park is carried out to facilities the community. This cultural park was designed under the name Aji Saka cultural park to commemorate the originator of javanes script, and use the Neo-Vernacular Architecture concept to maintain the existing culture and customs. Keywords : Grobogan Regency, Cultural Park, Aji Saka, Neo-Vernacular